1996
DOI: 10.1183/09031936.96.09020356
|View full text |Cite
|
Sign up to set email alerts
|

The role of thrombosis in severe pulmonary hypertension

Abstract: Considering the important surface in pulmonary circulation where blood can interact with the endothelium, the maintenance of blood fluidity through the lung, by antithrombotic pathways and products of the endothelium, is essential. This function appears to be ineffective in primary pulmonary hypertension and in severe secondary pulmonary hypertension. Thrombotic lesions are frequently found in pulmonary arteries in these diseases.Thrombin activity appears to be increased in severe pulmonary hypertension. Antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 82 publications
1
71
0
4
Order By: Relevance
“…Indeed, the blood level of fibrinopeptide A, which reflects thrombin activity, is markedly elevated in all patients with pulmonary arterial hypertension [17]. Whether these changes are a result of genetic deficiencies of antithrombotic pathways, or dysfunction of endothelial cells and/or platelets secondary to the pulmonary vascular injury, can be questioned.…”
Section: Cause Of Thrombi Formationsmentioning
confidence: 99%
“…Indeed, the blood level of fibrinopeptide A, which reflects thrombin activity, is markedly elevated in all patients with pulmonary arterial hypertension [17]. Whether these changes are a result of genetic deficiencies of antithrombotic pathways, or dysfunction of endothelial cells and/or platelets secondary to the pulmonary vascular injury, can be questioned.…”
Section: Cause Of Thrombi Formationsmentioning
confidence: 99%
“…An emerging role of release of platelet selective mediators, such as serotonin, thromboxane-A 2 and growth factors, in the development of CTEPH is under investigation [11]. It is not impossible that these factors may also induce changes in the adjacent lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the pulmonary arteries is a very common complication of many varieties of PH [105]. For example, CALVERLY et al [106] found that~50% of patients with cor pulmonale due to respiratory failure had pulmonary artery thrombosis at post mortem.…”
Section: The Role Of Pulmonary Endarterectomymentioning
confidence: 99%